The Development of The Situational Judgement Test (SJT): Workforce Agility - Helmi, Avin Fadilla; Marvianto, Ramadhan Dwi; Al Fariz, Arif Budiman; Anggoro, Indahinsani Purnasari; Anggoro, Wahyu Jati (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
This research aimed to develop a workforce agility measuring tool with the situational judgment test (SJT) format and evaluate its psychometric properties. This research included 886 respondents with higher education. The data were analyzed using confirmatory factor analysis (CFA) and multi-group confirmatory factor analysis (MGCFA). The CFA results showed that 18 items have satisfactory psychometric properties, thus forming a fit factor structure and providing validity evidence based on internal structure. Besides, the MGCFA results showed that this measuring instrument has measurement invariance at the strict invariance level to be used as validity evidence based on test consequences. The implication is that this measuring instrument has at least three of the five sources of validity to allow solid interpretations of the measuring results.